2022
DOI: 10.2147/nrr.s373694
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Workplace Incivility, Prosocial Motivation and Emotional Exhaustion to Thriving of Nurses

Abstract: Background:The study attempt to investigate the impact of individual-level factor (prosocial motivation), negative contextual factor (workplace incivility), and personal resource (emotional exhaustion) on the thriving of nurses. Methods: Primary data from 215 Pakistani nurses were collected and analyzed. Data were analyzed through the Second Synthetic Grey Relational Analysis (SSGRA) and the Regression Analysis. Results: We found that workplace incivility and thriving are negatively associated, whereas prosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
0
4
0
1
Order By: Relevance
“…13 Congruent to the psychology-derived literature, supportive work environments that provide training, recognition, guidance, and mentoring promote thriving in nursing. 14 In addition, some workplace constraints can inhibit nurses' ability to thrive. For example,…”
Section: Antecedents Of Thriving At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Congruent to the psychology-derived literature, supportive work environments that provide training, recognition, guidance, and mentoring promote thriving in nursing. 14 In addition, some workplace constraints can inhibit nurses' ability to thrive. For example,…”
Section: Antecedents Of Thriving At Workmentioning
confidence: 99%
“…Some organizational factors contributing to nurse thriving are empowerment, the mood of the organization, an enabling environment, organizational justice (perception of fairness and equality), togetherness with colleagues, and leaders' connectivity 13. Congruent to the psychology-derived literature, supportive work environments that provide training, recognition, guidance, and mentoring promote thriving in nursing 14…”
Section: Conceptual Model Of Thriving In Nursingmentioning
confidence: 99%
“…If the workplace environment is uncivil or toxic, it causes emotional exhaustion among employees and negatively influence their desires to thrive within organization (Nawaz et al, 2022;. the It has been reported that Amazon's offices valued productivity above all else, pushing their employees to their physical, mental, and emotional limits (Green America, 2022;Hill & Hill, 2021).…”
Section: Toxic Workplace Culturementioning
confidence: 99%
“…However, in the context of contemporary urban settings (Nawaz et al, 2020), the role of digital leadership is crucial for the establishment of sustainable enterprises. it is closely linked to developing innovative approaches for enhancing business intelligence (Nawaz et al, 2022b;Fritsch and Kublina, 2018). The advent of novel digital technologies is driving the latest economic boom and exerting a substantial influence on organizational management (Peng, 2022).…”
Section: Introductionmentioning
confidence: 99%